The Protective Effects and Mechanisms of Apelin/APJ System on Ischemic Stroke: A Promising Therapeutic Target - Tian, Yanjun; Chen, Ruijiao; Jiang, Yunlu; Bai, Bo; Yang, Tongju; Liu, Haiqing (Frontiers in Neurology, 2020)
The orphan receptor APJ and its endogenous ligand apelin, which are expressed in brain, are the major components of apelin/APJ system. Growing evidences show that apelin/APJ system plays a vital role in the pathophysiology of cerebral ischemic injury. Targeting apelin/APJ system may have protective effects on cerebral ischemic injury. In this review, we sum up the latest research progress relating to the actions and therapeutic potential of apelin/APJ system in ischemic stroke. An in-depth knowledge of the pathophysiological effects of apelin/APJ system and the underlying mechanisms will help to develop novel therapeutic interventions for ischemic stroke.